Analysis of Deformation Characteristics of Face Rockfill Dam with Crest Overflow in Feigu Reservoir During Operation - ZHAO Zejin; ZHOU Bin; LONG Jian; XI Lihua; ZHAN Jie (Renmin Zhujiang)
On the basis of the dam monitoring data,we analyze and evaluate dam deformation and dislocation distribution laws of spillway drain channels during operation upon the impounding of the face dam with crest overflow in Feigu Reservoir.The correlation analysis of environmental variables such as the reservoir water level,air temperature,and water temperature is carried out by means of mathematical statistics and spatiotemporal distribution analysis.It is concluded that the horizontal deformation and settlement of the dam crest are less than the safety warning values.Air temperature and the reservoir water level are the main environmental factors affecting dam deformation.The dislocation magnitude of the spillway drain channel is highly sensitive to temperature,but with coordinated deformation,adjacent drain channels have small disjunction momentum,and thus the spillway drain channel is in a safe state.We can reduce the uneven settlement of the spillway on the dam crest by mixing the main stone pile with a small amount of buried stone concrete.